Factors that affect the implementation of anti-corruption measures in concessioned projects in Chile. A case study - Mellado Peralta, Daniela; Moya Díaz, Emilio (Journal Studies of Public Policy, 2021)
This article seeks to identify the main factors that facilitate and limit the implementation of anti-corruption measures in concession projects in Chile. This is an area sensitive to corruption, as established in the 2015 Presidential Anti-Corruption Advisory Council report. The conceptual framework considers the “structural corruption” approach proposed by Sandoval. Likewise, the “anti-corruption strategies” approach was used. It proposes two strategies: classical and neo-institutional. The methodology used was qualitative. The main findings indicate that there is no specific anti-corruption approach. The areas most sensitive to corruption are those related to tax inspectors, technical consultancies and contract renegotiations. The main obstacles to the implementation of anti-corruption measures are: the wrong targeting of risks and the high demand for the work of the Coordination of Concessions. The main facilitating factor is the traceability of the processes in the concessioned projects.